Double- and Multi-Femtosecond Pulses Produced by Birefringent Crystals for the Generation of 2D Laser-Induced Structures on a Stainless Steel Surface - Fraggelakis, Fotis (Materials (Basel), 2019)
Laser-induced textures have been proven to be excellent solutions for modifying wetting, friction, biocompatibility, and optical properties of solids. The possibility to generate 2D-submicron morphologies by laser processing has been demonstrated recently. Employing double-pulse irradiation, it is possible to control the induced structures and to fabricate novel and more complex 2D-textures. Nevertheless, double-pulse irradiation often implies the use of sophisticated setups for modifying the pulse polarization and temporal profile. Here, we show the generation of homogeneous 2D-LIPSS (laser-induced periodic surface structures) over large areas utilizing a simple array of birefringent crystals. Linearly and circularly polarized pulses were applied, and the optimum process window was defined for both. The results are compared to previous studies, which include a delay line, and the reproducibility between the two techniques is validated. As a result of a systematic study of the process parameters, the obtained morphology was found to depend both on the interplay between fluence and inter-pulse delay, as well as on the number of incident pulses. The obtained structures were characterized via SEM (scanning electron microscopy) and atomic force microscopy. We believe that our results represent a novel approach to surface structuring, primed for introduction in an industrial environment.